The Bounty of the Sea and Long-Run Development - Carl-Johan Dalgaard; Anne Sofie B. Knudsen; Pablo Selaya (Center for Economic Studies and ifo Institute (CESifo), 2015)
What is the long run impact on development from differences in subsistence strategies during pre-industrial times? Whereas this question has been explored from the point of view of agriculture, remarkably little attention has been paid to the complementary strategy of relying on marine resources. As a step towards closing this gap, we construct an index - the Bounty of the Sea index - which captures the potential abundance of exploitable marine fish that individual countries have had access to, and proceed to explore its correlation with economic development. Our analysis reveals that a greater Bounty of the Sea stimulated pre-industrial development, and that countries inhabited by people with ancestry in regions with abundant marine resources are richer today. Probing possible underlying reasons, we find that populations with ancestry in regions rich in marine resources differ from societies with a purely agrarian legacy in terms of institutions, cultural values and average personality traits.
Keywords: O11; O13; O47; O57; 330; subsistence strategy; fishing; economic development; personality; culture; institutions